Model-Based Analysis of an Integrated Zinc-Air Flow Battery/Zinc Electrolyzer System - Lao-atiman, Woranunt; Bumroongsil, Kanya; Arpornwichanop, Amornchai; Bumroongsakulsawat, Palang; Olaru, Sorin; Kheawhom, Soorathep (Frontiers in Energy Research, 2019)
This work aims at analyzing an integrated system of a zinc-air flow battery with a zinc electrolyzer for energy storage application. For efficient utilization of inherently intermittent renewable energy sources, safe and cost-effective energy storage systems are required. A zinc-air flow battery integrated with a zinc electrolyzer shows great promise as an electricity storage system due to its high specific energy density at low cost. A mathematical model of the system was developed. The model was implemented in MATLAB and validated against experimental results. The validation of the model was verified by the agreement between the simulation and experimental polarization characteristic. The behavior and performance of the system were then examined as a function of different operating parameters: the flow rate of the electrolyte, the initial concentration of potassium hydroxide (KOH) and the initial concentration of zincate ion. These parameters significantly affected the performance of the system. The influence of the hydrogen evolution reaction (HER) on the performance of the system was investigated and discussed as it significantly affected the coulombic efficiencies of both the zinc-air flow battery and the zinc electrolyzer. Optimal KOH concentration was found to be about 6–7 M. Whilst increased KOH concentration enhanced the discharge energy of the battery, it also increased HER of both the battery and the electrolyzer. However, higher initial concentration of zincate ion reduced HER and improved the coulombic efficiency of the system. Besides, a higher flow rate of electrolyte enhanced the performance of the system especially at a high charge/discharge current by maintaining the concentration of active species in the cell. Nevertheless, the battery suffered from a higher rate of HER at a high flow rate. It was noted that the model-based analysis provided better insight into the behavioral characteristics of the system leading to an improved design and operation of the integrated system of zinc-air flow battery with the zinc electrolyzer.